Distorsi pesan dalam perpustakaan - Adul Karim Batubara (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2015)
The important role of communication for fundamental human life can not be denied. So is the case for the process of delivering information on the institution library. With good communication, the whole process of performance within the institution libraries can be run smoothly and successfully. Vice versa, less or even no communication actions in a library institution easily cause total failure of the whole process of the institution's own library. Effective communication is essential for all library institutions without exception. Therefore, the leadership of the institution of the library as the core communicator in an organization need to understand and fine-tune their communication skills in order to avoid misunderstandings in the delivery of the message.